Kate Chopin and Catholicism - Ostman, Heather. author. aut Link
XI, 229 p. 1 illus.
Keywords: ‘Heather Ostman’s Kate Chopin and Catholicism is meaty, interesting, and provocative. It may change the way we all read this marvel of a writer.’ — Linda Wagner-Martin, Professor of English and Comparative Literature at The University of North Carolina at Chapel Hill, USA, and author of Hemingway’s Wars: The Public and Private Battles (2017) ‘Heather Ostman’s Kate Chopin and Catholicism heralds an innovative methodology with rich possibilities for studies of Kate Chopin and American realism. As Chopin became immersed in the studies of Darwin, she drew away from practicing Catholicism. Ostman demonstrates how Chopin used Catholicism as a device to examine social issues and critique the schism between physical and corporeal pleasure. Ostman exemplifies how Chopin leveraged Catholicism to arrive at a revolutionary and unorthodox definition of mysticism and spirituality.’ — Kate O’Donoghue, Associate Professor of English, Suffolk County Community College, USA This book explores the Catholic aesthetic and mystical dimensions in Kate Chopin’s fiction within the context of an evolving American Catholicism in the late nineteenth and early twentieth centuries. Through a close reading of her novels and numerous short stories, Kate Chopin and Catholicism looks at the ways Chopin represented Catholicism in her work as a literary device that served on multiple levels: as an aesthetic within local color depictions of Louisiana, as a trope for illuminating the tensions surrounding nineteenth-century women’s struggles for autonomy, as a critique of the Catholic dogma that subordinated authenticity and physical and emotional pleasure, and as it pointed to the distinction between religious doctrine and mystical experience, and enabled the articulation of spirituality beyond the context of the Church. This book reveals Chopin to be not only a literary visionary but a writer who saw divinity in the natural world.